Energy Consumption Performance of a VTOL UAV In and Out of Ground Effect by Flight Test - Shanfei Su; Xiaowen Shan; Peng Yu; Hao Wang (Drones)
Current research on ground-effect unmanned aerial vehicles (UAVs) predominantly centers on numerical aerodynamic optimization and stability analysis in the ground effect, leaving a significant gap in the thorough examination of flight performance through flight tests. This study presents the design of a vertical takeoff and landing (VTOL) ground-effect UAV, featuring a vector motor configuration. The control system utilizes a decoupled strategy based on position and attitude, enabling stable altitude control in the low-altitude ground-effect region. Comprehensive flight tests were conducted to evaluate the UAV’s flight stability and energy consumption in the ground-effect region. The results reveal that the ground-effect UAV successfully performed rapid takeoff maneuvers and maintained stable forward flight in the designated ground-effect region. In the span-dominated ground-effect region, a significant 33% reduction in flight current was observed, leading to a corresponding 33% decrease in total power consumption compared to flight conditions outside the ground effect. These findings highlight a substantial improvement in flight performance under the influence of ground effect. The real-time flight data produced by this system provides valuable insights for optimizing the design of VTOL ground-effect UAVs.